ANALYSIS OF THE EFFECT OF TEMPERATURE AND HEATING TIME ON ASTM A572 STEEL AS A MATERIAL FOR MAKING INCINERATOR COMBUSTION CHAMBER ON THE RATE OF CORROSION - Nugroho, Eko; Rajabiyah, Nurlaila; Dharma, Untung Surya; Kristian, Latif (TURBO [Tulisan Riset Berbasis Online], 2025)
Corrosion is the degradation of metal quality caused by a reaction between the environment and the material. Generally, corrosion problems are caused by water. However, there are several factors other than water that influence the corrosion rate, such as temperature. An increase in temperature in a corrosive system will increase the rate of corrosion. This is caused by an increase in the active energy of the particles involved in the corrosion reaction. The aim of this research was to determine the effect of temperature and firing time on the corrosion rate of ASTM A 572 steel material. The research method used was experimental, using ASTM A 572 steel plates measuring 5 cm wide and 7 cm long with a thickness of 5 mm with the heating process used being 3 hours, 5 hours and 7 hours at temperatures of 600oC, 650oC and 700oC. The results of the research on the effect of temperature and firing time on the corrosion rate of ASTM A 572 steel material showed that the lowest average corrosion value was 0,3947 mm/year with a testing time of 3 hours at a temperature of 600oC. Then the highest average corrosion value was obtained, namely 8,0937 mm/year with a testing time of 7 hours at a temperature of 700oC